Pandemic mechanisms: puppet-making experiences and short scenes at home. (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
An report of the creative process of the Santa Catarina group Eranos Círculo de Artein a home environment during the pandemic, through the construction of puppets and creationof short scenes. Rod Puppets with a structure printed in 3d were developed based on the workof Hansjürgen Fettig, which gave rise to the short scenes Am(ar), Coração Inbox, ATempestade and Jornaleco. The impossibility of a face-to-face meeting with the audiencedrastically altered the group's theatrical production.
Keywords: pandemic; animation theatre; Eranos Círculo de Arte; Santa Catarina theater; mechanisms